2013
DOI: 10.1016/j.neuroimage.2013.04.049
|View full text |Cite
|
Sign up to set email alerts
|

Semantic versus perceptual interactions in neural processing of speech-in-noise

Abstract: Native listeners make use of higher-level, context-driven semantic and linguistic information during the perception of speech-in-noise. In a recent behavioral study, using a new paradigm that isolated the semantic level of speech by using words, we showed that this native-language benefit is at least partly driven by semantic context (Golestani et al., 2009). Here, we used the same paradigm in a functional magnetic resonance imaging (fMRI) experiment to study the neural bases of speech intelligibility, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
75
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 61 publications
(89 citation statements)
references
References 83 publications
(137 reference statements)
14
75
0
Order By: Relevance
“…This native-language benefit is thought to arise from greater use of top-down linguistic information to assist degraded speech comprehension. Using functional magnetic resonance imaging, we recently showed that left angular gyrus activation is modulated when semantic context is used to assist native language speech-in-noise comprehension (Golestani, Hervais-Adelman, Obleser, & Scott, 2013). Here, we extend the previous work, by reanalyzing the previous data alongside the results obtained in the non-native language of the same late bilingual participants.…”
mentioning
confidence: 56%
See 3 more Smart Citations
“…This native-language benefit is thought to arise from greater use of top-down linguistic information to assist degraded speech comprehension. Using functional magnetic resonance imaging, we recently showed that left angular gyrus activation is modulated when semantic context is used to assist native language speech-in-noise comprehension (Golestani, Hervais-Adelman, Obleser, & Scott, 2013). Here, we extend the previous work, by reanalyzing the previous data alongside the results obtained in the non-native language of the same late bilingual participants.…”
mentioning
confidence: 56%
“…during semantically unrelated trials, in which no supporting semantic information is available, c.f. Golestani et al, 2013) in both languages of participants.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Applying this framework to our experimental paradigm, one would expect that the responses in the auditory (i.e., lower‐level) areas decrease at the second compared to the first presentation of the distorted sentences since the prediction error (i.e., the mismatch between the internal model and the auditory input) diminishes compared to the prediction error at the initial exposure of the distorted sentence when no predictive information is available. However, most of the previous fMRI studies that have used related experimental paradigms have not found the activity within the primary auditory cortex and surrounding areas to be modulated (Golestani, Hervais‐adelman, Obleser, & Scott, 2013; Hervais‐Adelman et al., 2012; Tuennerhoff & Noppeney, 2016; Zekveld et al., 2012; see also Wild et al., 2012a) when distorted speech of low initial intelligibility is rendered more intelligible by a prior or coincident presentation of a disambiguating stimulus. To explain these unexpected results, Wild et al.…”
Section: Discussionmentioning
confidence: 99%